Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7ra06327j
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(ii)-8-hydroxyquinoline-5-sulfonic acid complex/N-(4-aminobutyl)-N-ethylisoluminol/reduced graphene hybrids as nanocatalytic reaction platforms for chemiluminescence

Abstract: The as-prepared CoII(HQS)2/ABEI/rGO hybrids exhibited excellent CL activity when reacted with hydrogen peroxide, the dissolved oxygen and periodate in alkaline solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Compared with the C 1s spectrum of Pdots, the binding energy of CO of ABEI-Pdots dropped about 1 eV from 288.8 to 287.9 eV, which was due to the formation of amide bonds in the ABEI-Pdots. ,, In addition, the proportion of CO double bonds slightly raised from 2.88% to 3.44%, originating from ABEI molecules (Table S1). More obviously, the deconvolution of the N 1s spectrum from the ABEI-Pdots showed three curved-fitted components peak at 399.3, 400.7, and 402.9 eV (Figure F), which were contributed to the -N–sp 3 C, -N–sp 2 C, and N–O, respectively . The -N–sp 3 C and -N–sp 2 C bonds were originated from ABEI molecules, while these bonds did not exist in the Super Yellow and PSMA polymer (Scheme , the structure of Super Yellow and PSMA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the C 1s spectrum of Pdots, the binding energy of CO of ABEI-Pdots dropped about 1 eV from 288.8 to 287.9 eV, which was due to the formation of amide bonds in the ABEI-Pdots. ,, In addition, the proportion of CO double bonds slightly raised from 2.88% to 3.44%, originating from ABEI molecules (Table S1). More obviously, the deconvolution of the N 1s spectrum from the ABEI-Pdots showed three curved-fitted components peak at 399.3, 400.7, and 402.9 eV (Figure F), which were contributed to the -N–sp 3 C, -N–sp 2 C, and N–O, respectively . The -N–sp 3 C and -N–sp 2 C bonds were originated from ABEI molecules, while these bonds did not exist in the Super Yellow and PSMA polymer (Scheme , the structure of Super Yellow and PSMA).…”
Section: Resultsmentioning
confidence: 99%
“…More obviously, the deconvolution of the N 1s spectrum from the ABEI-Pdots showed three curvedfitted components peak at 399.3, 400.7, and 402.9 eV (Figure 1F), which were contributed to the -N−sp 3 C, -N−sp 2 C, and N− O, respectively. 59 The -N−sp 3 C and -N−sp 2 C bonds were originated from ABEI molecules, while these bonds did not exist in the Super Yellow and PSMA polymer (Scheme 1, the structure of Super Yellow and PSMA). The N−O bond at 402.9 eV was likely originated from NHS cross-linking agent without complete filtration or ABEI-Pdots oxidation during XPS sample preparation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…There were two main reasons accounting for this phenomenon. On one hand, it was well-known that the CL reaction of ABEI–H 2 O 2 system was carried out in alkaline solution because higher pH could accelerate the decomposition of H 2 O 2 and the deprotonation of ABEI, which in turns enhanced CL emission. , On the other hand, the CL kinetic curves of PMAANGs-ABEI/Co 2+ with H 2 O 2 at pH 12.0 and 13.0 were analyzed as shown in Figure S5. It was found that the CL kinetic curve at pH 12.0 was obviously slower than that at pH 13.0.…”
Section: Resultsmentioning
confidence: 99%
“…5,6 The synthesis methods are mainly divided into two categories: (a) Chemiluminescent molecules are loaded through noncovalent bonds, such as Au− N bonds, hydrogen bonds, and π−π stacking. 4,5,7,8 However, most of the CFNMs synthesized by these methods have disadvantages of reagent shedding and leakage, which reduces the chemiluminescence (CL) stability of CFNMs and affects the reproducibility of bioassays. (b) Chemiluminescent molecules are loaded through covalent bonds.…”
mentioning
confidence: 99%
“…The C 1s and N 1s spectra of g-C 3 N 4 /ABEI showed new deconvolution peaks at 288.5 and 400.4 eV compared with g-C 3 N 4 , corresponding to the O C−N−N−CO moiety in ABEI. 30,31 The C 1s spectrum of g-C 3 N 4 /ABEI could be resolved into four components centered at ∼288.5, 288.1, 285.5, and 284.8 eV, representing N−CO in ABEI, N−CN in triazine rings, sp 3 C−C, and sp 2 CC, respectively (Figure 2b). Moreover, as a result of ABEI implementation to the g-C 3 N 4 nanosheets, the two main C 1s splitting peak ratios at 282.2 and 284.8 eV (I 282.2 /I 284.8 ) of g-C 3 N 4 /ABEI were increased to 1.6:1, relatively higher than that of g-C 3 N 4 (1.3:1).…”
Section: ■ Results and Discussionmentioning
confidence: 99%